Ultra-long-acting in-situ forming implants with cabotegravir protect female macaques against rectal SHIV infection - Isabella C. Young; Ivana Massud; Mackenzie L. Cottrell; Roopali Shrivastava; Panita Maturavongsadit; Alka Prasher; Andres Wong-Sam; Chuong Dinh; Tiancheng Edwards; Victoria Mrotz; James Mitchell; Josilene Nascimento Seixas; et al. (Nature Communications, 2023)
Abstract Ultra-long-acting delivery platforms for HIV pre-exposure prophylaxis (PrEP) may increase adherence and maximize public health benefit. We report on an injectable, biodegradable, and removable in-situ forming implant (ISFI) that is administered subcutaneously and can release the integrase inhibitor cabotegravir (CAB) above protective benchmarks for more than 6 months. CAB ISFIs are well-tolerated in female mice and female macaques showing no signs of toxicity or chronic inflammation. In macaques, median plasma CAB concentrations exceed established PrEP protection benchmarks within 3 weeks and confer complete protection against repeated rectal SHIV challenges. Implant removal via a small incision in 2 macaques at week 12 results in a 7- to 48-fold decrease in plasma CAB levels within 72 hours. Modeling to translate CAB ISFI dosing suggests that a 3 mL injection would exceed protective benchmarks in humans for over 5 months post administration. Our results support the clinical advancement of CAB ISFIs for ultra-long-acting PrEP in humans.